2020
DOI: 10.1016/j.celrep.2020.107988
|View full text |Cite
|
Sign up to set email alerts
|

Input-Output Relationship of CA1 Pyramidal Neurons Reveals Intact Homeostatic Mechanisms in a Mouse Model of Fragile X Syndrome

Abstract: Summary Cellular hyperexcitability is a salient feature of fragile X syndrome animal models. The cellular basis of hyperexcitability and how it responds to changing activity states is not fully understood. Here, we show increased axon initial segment length in CA1 of the Fmr1 −/y mouse hippocampus, with increased cellular excitability. This change in length does not result from reduced AIS plasticity, as prolonged depolarization induces changes in AIS length indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 82 publications
15
50
1
Order By: Relevance
“…Two photon Ca 2+ imaging demonstrated that synaptically evoked dendritic Ca 2+ signals were consistently smaller in fmr1 KO neurons. In agreement with a previous study, we found that basal synaptic transmission at TA synapses was not different between wild type and fmr1 KO mice as has been described previously 10 (but see 11 ). There was no difference in the function of NMDARs, dendritic complex spikes, or isolated dendritic Ca 2+ spikes between wild type and fmr1 KO CA1 pyramidal neurons.…”
Section: Discussionsupporting
confidence: 94%
“…Two photon Ca 2+ imaging demonstrated that synaptically evoked dendritic Ca 2+ signals were consistently smaller in fmr1 KO neurons. In agreement with a previous study, we found that basal synaptic transmission at TA synapses was not different between wild type and fmr1 KO mice as has been described previously 10 (but see 11 ). There was no difference in the function of NMDARs, dendritic complex spikes, or isolated dendritic Ca 2+ spikes between wild type and fmr1 KO CA1 pyramidal neurons.…”
Section: Discussionsupporting
confidence: 94%
“…Importantly, while activity-dependent changes in both AIS position and length have been described in cultured neurons ( Grubb and Burrone, 2010 ; Evans et al, 2013 , 2015 ; Muir and Kittler, 2014 ; Chand et al, 2015 ; Horschitz et al, 2015 ; Wefelmeyer et al, 2015 ; Dumitrescu et al, 2016 ; Lezmy et al, 2017 ; Sohn et al, 2019 ; Booker et al, 2020 ), plasticity of AIS position without any accompanying length change has yet to be described in intact networks. Indeed, to date, all activity-dependent AIS plasticity described in vivo or in ex vivo acute slices seems to express itself as length changes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Slices containing LPC lesion and PBS control neurons were prepared from mice which had been implanted with cryogels overlaying the motor cortex (M1), as previously described [5,6]. Briefly, mice were sedated with isofluorane, decapitated and their brains rapidly removed and placed in ice-cold sucrose-modified artificial cerebrospinal fluid (sucrose-ACSF; in mM: 87 NaCl, 2.5 KCl, 25 , containing 500 nM tetrodotoxin,TTX) and bubbled with carbogen, at a rate of 4-6 mL.min −1 , recordings were maintained at 30 ± 1 °C with an inline Peltier heating device (Scientifica, Brighton, UK).…”
Section: In Vitro Slice Electrophysiologymentioning
confidence: 99%